Microparticles coated with proteins in their natural state and in vitro gastrointestinal simulation. - Rengifo Silvano, Estefany Deyhanyra (2022)
This study aimed to produce pectin and alginate microparticles by ionic gelation coated with different concentrations of bovine blood and egg white protein in their natural state. The coated microparticles were characterized, and their physical resistance and morphology were evaluated, as well as the released protein during in vitro gastrointestinal simulation. The highest protein adsorption (65.47%) was shown by pectin microparticles coated with bovine blood (10%), regardless of the protein type and concentration used. Likewise, higher amounts of adsorbed protein resulted as protein concentration increased, regardless of the type of microparticle. Nevertheless, the physical resistance of coated microparticles was affected more by the type of polysaccharide, being alginate microparticles more resistant. Adsorbed proteins on microparticles surface showed higher solubility values in vitro gastrointestinal simulation regardless of protein type. Bovine blood and egg white proteins in their natural state can be used as alternative coating materials for microparticles